EFFECT OF BUNCH LOAD ON THE QUALITY OF CARDINAL GRAPE VARIETY - PRCULOVSKI, Zlatko; PETKOV, Mihail; BOSKOV, Krum; KRYEZIU, Sami (Journal Agriculture and Forestry, 2021)
Our research aims to evaluate the effect of bunch load variation per unit area on the quality of Cardinal table grape variety. The experiments were carried out during three vegetation seasons (2014 – 2016) on Cardinal grape variety grown on pergola training system, with a planting distance of 2.5 m x 2.5 m, in Gevgelija-Valandovo vine growing region, the Republic of Macedonia. After the blooming phenophase, the number of bunches (crop load) was reduced. Three bunch thinning variants were applied: V1 (thinning to 3 bunches/m2 ), V2 (thinning to 4 bunches/m2 ) and V3 (thinning to 5 bunches/m2 ). They were then compared with the standard (ST) where no thinning of bunches was applied. Research results show that bunch load in Cardinal variety has a significant impact on bunch and berry mass, transportability, maturation dynamics and packed grape quantity and that the V1 variant, with the lowest bunch density per m 2 , has the largest individual bunch and berry mass (502.3 g and 8.83 g respectively), while the ST variant yielded the smallest bunch and berry mass (451.7 g and 7.93 g respectively). We got similar results on grape transportability marked by berry firmness and berry adherence strength. The largest quantity of total harvested grapes was obtained in the V3 (2.22 kg/m2 ) and ST (2.19 kg/m2 ) variants, while the smallest quantity of total harvested grapes (1.47 kg/m2 ) was obtained in the V1 variant. The largest quantity of packed grapes (1.87 kg/m2 ) was obtained in the V2 variant, and the smallest in the V1 variant (1.44 kg/m2 ).
Keywords: table grapes, bunch thinning, bunch mass, berry mass, quantity of packed grapes